n-3 PUFA Esterified to Glycerol or as Ethyl Esters Reduce Non-Fasting Plasma Triacylglycerol in Subjects with Hypertriglyceridemia: A Randomized Trial - Hedengran, Anne; Szecsi, Pal B.; Dyerberg, Jørn; Harris, William S.; Stender, Steen (Lipids, 2015)
To date, treatment of hypertriglyceridemia with long-chain n-3 polyunsaturated fatty acids (n-3 PUFA) has been investigated solely in fasting and postprandial subjects. However, non-fasting triacylglycerols are more strongly associated with risk of cardiovascular disease. The objective of this study was to investigate the effect of long-chain n-3 PUFA on non-fasting triacylglycerol levels and to compare the effects of n-3 PUFA formulated as acylglycerol (AG-PUFA) or ethyl esters (EE-PUFA). The study was a double-blinded randomized placebo-controlled interventional trial, and included 120 subjects with non-fasting plasma triacylglycerol levels of 1.7–5.65 mmol/L (150–500 mg/dL). The participants received approximately 3 g/day of AG-PUFA, EE-PUFA, or placebo for a period of eight weeks. The levels of non-fasting plasma triacylglycerols decreased 28 % in the AG-PUFA group and 22 % in the EE-PUFA group ( P < 0.001 vs. placebo), with no significant difference between the two groups. The triacylglycerol lowering effect was evident after four weeks, and was inversely correlated with the omega-3 index (EPA + DHA content in erythrocyte membranes). The omega-3 index increased 63.2 % in the AG-PUFA group and 58.5 % in the EE-PUFA group ( P < 0.001). Overall, the heart rate in the AG-PUFA group decreased by three beats per minute ( P = 0.045). High-density lipoprotein (HDL) cholesterol increased in the AG-PUFA group ( P < 0.001). Neither total nor non-HDL cholesterol changed in any group. Lipoprotein-associated phospholipase A2 (LpPLA2) decreased in the EE-PUFA group ( P = 0.001). No serious adverse events were observed. Supplementation with long-chain n-3 PUFA lowered non-fasting triacylglycerol levels, suggestive of a reduction in cardiovascular risk. Regardless of the different effects on heart rate, HDL, and LpPLA2 that were observed, compared to placebo, AG-PUFA, and EE-PUFA are equally effective in reducing non-fasting triacylglycerol levels.